Application of the Pentahelix Model in Increasing Tourist Visits to the Tempe Lake Festival in Wajo Regency - I Nyoman Siryayasa; Nur Farah Fajriaty Muchlis; Ernawati Ab; Andika Isma (SEULANGA SYSTEM PUBLISHER, 2024)
This study aims to evaluate the efforts of the Tempe Lake Festival organizers in increasing tourist visits in Wajo Regency through the application of the Pentahelix model. The method used is descriptive qualitative with data collection techniques through observation, interviews, and literature study. The results showed that collaborative involvement between the government, academics, media, businesses, and the community proved effective in attracting tourists and promoting local cultural wealth. The Pentahelix model made a significant contribution by strengthening the network of cooperation and synergy between various related parties, thus increasing the overall attractiveness of the festival. Although the festival faced challenges in the form of weather changes that impacted accessibility and event implementation, it is recommended that organizers strengthen infrastructure and add activities that are not dependent on weather conditions. This research is expected to be an important reference in the development of collaboration-based tourism strategies and contribute to the literature related to the Tempe Lake Festival case study as a model of Pentahelix implementation in the tourism industry.